Comparison of patient evaluations of health care quality in relation to WHO measures of achievement in 12 European countries - Kerssens Jan J.; Groenewegen Peter P.; Sixma Herman J.; Boerma Wienke G.W; Eijk Ingrid van der (The World Health Organization, 2004)
OBJECTIVES: To gain insight into similarities and differences in patient evaluations of quality of primary care across 12 European countries and to correlate patient evaluations with WHO health system performance measures (for example, responsiveness) of these countries. METHODS: Patient evaluations were derived from a series of Quote (QUality of care Through patients' Eyes) instruments designed to measure the quality of primary care. Various research groups provided a total sample of 5133 patients from 12 countries: Belarus, Denmark, Finland, Greece, Ireland, Israel, Italy, the Netherlands, Norway, Portugal, United Kingdom, and Ukraine. Intraclass correlations of 10 Quote items were calculated to measure differences between countries. The world health report 2000 - Health systems: improving performance performance measures in the same countries were correlated with mean Quote scores. FINDINGS: Intra-class correlation coefficients ranged from low to very high, which indicated little variation between countries in some respects (for example, primary care providers have a good understanding of patients' problems in all countries) and large variation in other respects (for example, with respect to prescription of medication and communication between primary care providers). Most correlations between mean Quote scores per country and WHO performance measures were positive. The highest correlation (0.86) was between the primary care provider's understanding of patients' problems and responsiveness according to WHO. CONCLUSIONS: Patient evaluations of the quality of primary care showed large differences across countries and related positively to WHO's performance measures of health care systems.